African perspectives on climate change research - Al-Zu’bi, Maha; Dejene, S.W.; Hounkpe, J.; Kupika, O. L.; Lwasa, S.; Mbenge, M.; Mwongera, Caroline; Ouédraogo, Moctar; Toure, N. E. (Springer, 2022)
The 27th Conference of the Parties (COP27) is being held in November 2022 in Sharm el-Sheikh, Egypt. Having a climate summit hosted in an African country makes it timely to highlight climate change research from the continent. We asked a selection of researchers to share their thoughts on current research questions and how they affect African responses to climate change.